Determination of male-specific gene expression of White Lamphun cattle semen treated by monoclonal antibodies - DUMRONGSRI, SIRIKRON; KHAMLOR, T; PONGPIACHAN, P; SRINGARM, K (The Indian Journal of Animal Sciences, 2016)
In the present study, male-specific monoclonal antibodies, P1C2B8 and P1C2C9, were used for sperm sexing via agglutination and cytotoxic reactions in White Lamphun cattle semen no. 862, no. 863 and no. KL. Live sperm percentage was used to find out an optimum dilution of antibody in agglutination and cytotoxic reactions and multiplex real time polymerase chain reaction was used to determine male-specific gene expression in each optimum dilution. In agglutination treatment, the results showed that all cattle had the same optimum antibody dilution while in cytotoxicity treatment, each cattle had different optimum antibody dilution. The results from multiplex real time polymerase chain reaction also showed that in both agglutination and cytotoxicity treatments, male- specific gene expression in semen samples was lower in cattle no. 862, no. 863 and no. KL when compared to control treatment. From these results, it was implied that antibodies P1C2B8 and P1C2C9 could alter the sperm sex ratio by reducing Y sperm in White Lamphun cattle semen.